2013
DOI: 10.1007/s11482-013-9246-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Easy Access Related to Better Life? Walkability and Overlapping of Personal and Communal Identity as Predictors of Quality of Life

Abstract: Two studies (N = 190 and N = 447) were conducted to investigate the link between living in walkable neighborhoods and satisfaction with life in a city. Additionally, we explore possible mediators of this relationship. In both studies walkability was a significant predictor of perceived quality of life in a city, and overlap between personal and communal identity (in Study 1 and Study 2) and city identification (Study 2) were mediators of the walkability—quality of life relation. Implications for research on en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
2
21
0
3
Order By: Relevance
“…Walkability, which has been shown to be associated with better physical health [66] or human well-being [67], has been a popular topic of research in recent years. Several reviews addressed already the influence of the neighborhood environment on walkability [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Walkability, which has been shown to be associated with better physical health [66] or human well-being [67], has been a popular topic of research in recent years. Several reviews addressed already the influence of the neighborhood environment on walkability [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the level of fusion between personal and group identities, I used the Polish version (Besta, Jaśkiewicz & Besta, 2014) of the seven-item identity fusion scale (Gómez et al, 2011b). The feeling of unity with one's country ("I am one with my country," "I feel immersed in my country," "I have a deep emotional bond with my country," "My country is me," "I would do more for my country than any of the other group members would," "I am strong because of my country," "I make my country strong") and with gender (e.g., "I feel one with my gender") were measured separately.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…Several previous studies have revealed the presence of a relationship between the built environment and a willingness to engage in physical activities [5,6]. A more walkable built environment has also been related to a higher perceived quality of life in the city [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The relationship between neighbourhood walkability and identity-related variables has been tested in the context of the quality of life [7]. Neighbourhood walkability has also been linked to social cohesion [21], and a pedestrian-oriented neighbourhood is expected to encourage the residents to interact [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation